INTEGRAL AND QUANTITATIVE APPROACHES IN THE ANALYSIS OF THE TAX POTENTIAL OF FINANCIAL MARKET - T. Paientko (Kherson State University, 2012)
Article is devoted the analysis of tax potential of the financial market. The necessities of applying quantitative and integrated approaches to the assessment of the tax potential of the financial market are substantiated.